Pengaruh Terapi AIUEO terhadap Kemampuan Bicara Pasien Stroke yang Mengalami Afasia Motorik (Journal of Telenursing (JOTING), 2019)
The purpose of this study was to determine the effect of AIUEO therapy on the speech ability of stroke patients who have motor aphasia in Raja Ahmad Thabib Hospital Tanjungpinang. The research design used was quasi experiment with the Nonequivalent Control Group Design approach. The results showed that there were significant differences in the functional ability of communication between the control and treatment groups with a value of p